(untitled) (Baghdad Science Journal, 2025)
Density Functional Theory (DFT) calculations were carried out to study the thermal cracking for acenaphthylene molecule to estimate the bond energies for breaking C8b-C5a , C5a-C5 , C5-C4 , and C5-H5 bonds as well as the activation energies. It was found that for C8b-C5a , C5-C4 , and C5-H5 reactions it is often possible to identify one pathway for bond breakage through the singlet or triplet states. The atomic charges , dipole moment and nuclear – nuclear repulsion energy supported the breakage bond .Also, it was found that the activation energy value for C5-H5 bond breakage is lower than that required for C8b-C5a , C5a-C5 , C5-C4 bonds which refer to C5-H5 bond in acenaphthylene molecule are weaker than C8b-C5a , C5a-C5 , C5-C4 bonds .It is reasonable to presume that C5-H5 bonds are broken first when a acenaphthylene molecule is exposed to thermal cracking. It seems that the characteristic planarity for the polyaromatic hydrocarbons is an important factor to acquire the molecule structure of the required stability along the reaction path . The trends in the bond energies and the configuration structures are discussed .